NEUROFIBROMATOSIS TYPE 1 ASSOCIATED WITH PHEOCHROMOCYTOMA-CASE REPORT - Bajraktarova prosheva, Tatjana; Todorova, Biljana; Stevchevska, Aleksandra; Bitoska, Iskra (My University, 2022)
Introduction: Neurofibromatosis type 1 is an autosomal dominant disease caused by a genetic mutation of the neurofibromin1 gene located on chromosomal segment 17q11.2 on the long arm of chromosome 17. It occurs in 1:4000 individuals. Besides of typical neurofibromas, it is often associated with other tumors: pheochromocytoma, astrocytoma, rhabdomyosarcoma, carcinoid of the duodenum, somatostatinoma, adenoma of the parathyroid gland. Pheochromocytoma is a neuroendocrine tumor originating from the chromaffin cells of the adrenal medulla with an incidence of 1:100,000 inhabitants per year and a prevalence of 8:1,000,000 population. Case report: A 65-year-old male patient was admitted to our hospital for examination of a right adrenal mass with dimensions of 55x55 mm seen on ultrasound. The diagnosis of neurofibromatosis is histologically confirmed before puberty. Status praesens: multiple neurofibromatous lesions of the trunk, hypertension of 210/110 mmHg, tachycardia of 125/min. An abdominal CT scan was performed with the finding of a round, hypodense mass with dimensions of 5 cm on the right adrenal gland. Left adrenal gland was normal. The laboratory showed elevated urinary catecholamines: VMA 81.9 µmol/dU(7.0-68 µmol/dU) metanephrine 10.4 µmol/dU(Do 5.5 µmol/dU), thus the diagnosis of pheochromocytoma was confirmed. A right adrenalectomy was performed. Postoperative control catecholamines: VMA: 17.3/26.4/26.6 µmol/dU; Metanephrine: 2.0/1.5/1.0 µmol/dU; Pathohistological finding: Well-defined nests of polygonal cells surrounded by fibrovascular stroma. Conclusion: Due to the genetic predisposition, in patients with NF1 the development of Tu other than neurofibromas should be considered. Screening of patients with NF1 for pheochromocytoma by determination of catecholamines in 24 h urine is recommended, as one in 48 patients with NF1 develops pheochromocytoma.